2003
DOI: 10.1046/j.1365-2249.2003.02047.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitrodendritic cell-induced T cell responses to B cell chronic lymphocytic leukaemia enhanced by IL-15 and dendritic cell–B-CLL electrofusion hybrids

Abstract: SUMMARYHLA class II-restricted proliferative and cytotoxic T cell (CTL) responses to B cell chronic lymphocytic leukaemia (B-CLL) can be generated using autologous dendritic cells (DCs) pulsed with tumour cell lysate. In this study a number of different approaches were used to optimize further the in vitro system. First, the effects of a variety of maturation agents were studied. The addition of TNF-a , polyriboinosinic polyribocytidylic acid (Poly(I:C)) and LPS to autologous DCs resulted in the emergence of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 35 publications
1
19
1
1
Order By: Relevance
“…a lectin such as Pokeweed mitogen (PWM), was observed in a mixed lymphocyte reaction after single presensitization. The impaired T-cell reactivity in B-CLL patients might be explained by the influence of CD19 + /CD5 + leukemic cells or T regulatory cells on T-cell function as well as on the DC population (5,51) and might be overcome by specific adjuvants, such as IL-12, IL-15 or sCD40L (52,53). After 2 weeks of presensitization, we observed CD8 + T-cells reactive to PWM, IMP peptide or RHAMM/CD168 peptide in another cohort of B-CLL patients (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…a lectin such as Pokeweed mitogen (PWM), was observed in a mixed lymphocyte reaction after single presensitization. The impaired T-cell reactivity in B-CLL patients might be explained by the influence of CD19 + /CD5 + leukemic cells or T regulatory cells on T-cell function as well as on the DC population (5,51) and might be overcome by specific adjuvants, such as IL-12, IL-15 or sCD40L (52,53). After 2 weeks of presensitization, we observed CD8 + T-cells reactive to PWM, IMP peptide or RHAMM/CD168 peptide in another cohort of B-CLL patients (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, the fusion vaccine EC109-DC, was made from amalgamation of DC, which was induced by combining cytokine from CD34+ hematopoietic stem cells isolated from the cord blood, and the EC109 by traditional Consequently, it is more effective and practical to fuse vaccine with DC than a single antigen in theory [12][13][14] . Some curative effects of fusion vaccine with DC have been seen in clinic experiments [15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…However, Goddard et al have shown that with the appropriate culture conditions, including additional cytokines, morphologically and functionally normal DCs can be generated from patients with B-CLL. 10,11 CLL-DCs were morphologically and phenotypically immature, lacking the maturation antigen CD83 and the costimulatory molecule CD80 and therefore being unable to induce a significant response in an allogeneic mixed lymphocyte reaction (MLR) with a reduced ability to release IL-12 and driven to a Th2 response. Only weak T-cell responses against unstimulated CLL cells have been observed in autologous MLRs.…”
Section: Toxicitymentioning
confidence: 99%
“…[8][9][10] The stimulation of T cells by tumor cell lysate-pulsed DCs has been demonstrated in vitro in B-CLL. 10,11 We therefore wondered if the application of ex vivogenerated dendritic cells (DCs) pulsed with tumor lysates or apoptotic bodies might help to improve the antileukemic immune response in B-CLL patients.…”
Section: Introductionmentioning
confidence: 99%